Pleurosigma guarreranum, sp. nov. (Pleurosigmataceae, Bacillariophyta), from the Gulf of San Matías, Argentina, and comparison with the allied species Pleurosigma exemptum and P. obesum - Sunesen, Inés (2013)
A new marine diatom, Pleurosigma guarreranum Sar, Sterrenburg & Sunesen, sp. nov., is described with light and electron microscopy from material collected in coastal waters of the Gulf of San Matías, Río Negro Province, Argentina. Pleurosigma guarreranum resembles P. exemptum and P. obesum from the Philippines. Isotypes of P. exemptum and P. obesum deposited in the Albert Mann Collection, National Museum of Natural History, Smithsonian Institution (US), were examined with light microscopy. The observations supported a previous suggestion to include P. obesum as a heterotypic synonym of P. exemptum, which has priority. Since there is no available unmounted original material of P. exemptum, a comparative light microscopical analysis of P. guarreranum and the type material of P. exemptum was made. Despite some similarities, there are subtle differences in morphometric data, valve outline, raphe sternum pattern, and morphology of the central area. But especially, the two species consistently differ in the angle of intersection of the oblique striae, justifying a separate taxonomic position. Pleurosigma guarreranum was also compared with another species belonging to the section Formosi, P. decorum, similar in valve outline, raphe sternum pattern and angle of intersection of the oblique striae.